2019
DOI: 10.1371/journal.ppat.1007717
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans induces mucosal bacterial dysbiosis that promotes invasive infection

Abstract: Infectious complications are a common cause of morbidity and mortality in cancer patients undergoing chemotherapy due to increased risk of oral and gastrointestinal candidiasis, candidemia and septicemia. Interactions between C . albicans and endogenous mucosal bacteria are important in understanding the mechanisms of invasive infection. We published a mouse intravenous chemotherapy model that recapitulates oral and intestinal mucositis, and myelosuppression in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
137
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(150 citation statements)
references
References 76 publications
7
137
2
4
Order By: Relevance
“…It is possible that, like lactobacilli, endogenous streptococcal species have antagonistic relationships with C. albicans. Of note, S. oralis and other human streptococcal species with symbiotic relationships with this fungus are not part of the mouse microbiome [18,33,40]. However, we have reported a symbiotic relationship between oral endogenous enterococci and C. albicans in mice [33], consistent with the reduction in the abundance of these organisms in mice receiving sucrose that have reduced C. albicans burdens.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It is possible that, like lactobacilli, endogenous streptococcal species have antagonistic relationships with C. albicans. Of note, S. oralis and other human streptococcal species with symbiotic relationships with this fungus are not part of the mouse microbiome [18,33,40]. However, we have reported a symbiotic relationship between oral endogenous enterococci and C. albicans in mice [33], consistent with the reduction in the abundance of these organisms in mice receiving sucrose that have reduced C. albicans burdens.…”
Section: Discussionsupporting
confidence: 61%
“…Tongue bacterial DNA and sequencing was performed using a lysis protocol and sequencing analysis pipeline optimized for mucosal microbiome characterization in murine tongue tissues [33]. The V4 region was amplified using 515F and 806R primers with Illumina adapters and bar codes on the 3′ end.…”
Section: S Rrna Gene High-throughput Sequencingmentioning
confidence: 99%
“…The oral microbiome is one of the most complex environments harboring diverse microbiota that co-exist in equilibrium (Wade, 2013;Krom et al, 2014;Xu and Dongari-Bagtzoglou, 2015;Sultan et al, 2018). This equilibrium is crucial for maintaining oral health as an imbalance potentiates the dominance of pathogenic species, which may lead to the development of disease (Jenkinson and Lamont, 2005;Duran-Pinedo and Frias-Lopez, 2015;Bertolini et al, 2019). In the oral cavity, microorganisms exist within highly organized and structured microbial communities referred to as biofilms, where microbial cells are embedded within a self-produced extracellular polymeric substance (Jenkinson et al, 1990;Kolenbrander et al, 2002;Rickard et al, 2003;Vu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, investigators demonstrated that the oral microbiome is disrupted by 5-fluorouracil (5-FU) and doxorubicin chemotherapy, but they did not observe major changes in the composition of the mycobiome (13). Moreover, mice receiving both 5-fluorouracil and C. albicans had a loss of bacterial diversity and showed endogenous overgrowth of organisms such as Enterococcus and Stenotrophomonas in the oral mucosa (14). In addition to chemotherapy, antimicrobial therapy, a very common practice in this patient population, impacts mycobiome composition.…”
mentioning
confidence: 99%
“…This effect was not seen in other taxa analyzed (data not shown). To our knowledge, the changes in the oral mycobiome occurring as a result of chemotherapy have been studied only in regard to their role in chemotherapy-induced mucositis in the setting of 5-fluorouracil (5-FU) or doxorubicin-based chemotherapy in mice and humans (13,14). In patients, although the authors expected chemotherapy to affect the oral mycobiome, no major changes in the composition of fungal communities were observed (13).…”
mentioning
confidence: 99%